¿Ideal democrático? Del activismo judicial a la constitucionalización del derecho. (2013)
The constitutionalization of law in Colombia is due to an active participation of the judge; in particular; of the constitutional judge. The judicial precedent source of law is an example of the inclusion of the judge on the constitutional stage as guarantor of democracy and law. The democratic ideal irreversibly includes the constitutional judge and his interpretations. The overinterpretation of law answers to a broad interpretation of the Constitution and to a building of norms that contribute something to fill the gaps in the law. Thus neoconstitutionalism is constitutionalizing the juridical order.